PENGEMBANGAN BUKU AJAR BAHASA INDONESIA BERBASIS PENDIDIKAN KARAKTER DENGAN MODEL ASSURE PADA SISWA SEKOLAH DASAR - Antonius Wicaksono Alam; Hanif Fikri Bariska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2018)
Text book is material used by the students for helping the achievement of the competency standard , the purpose of education of primary and competence have (Depdiknas.2006). Of research, development text book based character education with a assure model on primary school student aimed at for (1) know the process of development text book Indonesian language based character education by using assure kind of classroom in primary school student, (2) know the quality of teks book Indonesian language based character education by using assure kind of classroom in primary school student. This research using kind of research development (research and development). A design study on four-D oriented model consisting of 4 steps in the define, design , develop, and disseminate. Data collection techniques used in the process of define used technique documentation main competence (KI) and basic competence (KD) in 2013 curriculum. Data collection techniques used in the process of design validation the technique, observation, the survey, and tests used to measure product quality based on terms of use.The result of developing teks book based character education with a assure model on primary school student that have been validated to the quality of the books according to components teaching material, the appearance of, language and graphic reached the percentage of the respective components 98,9 % , 100 % , 96,4 % , 94,8 % . The result of the observation for the use of the activity of teachers text book components, the activity of students and response students show the percentage of the respective components 93.5 %, 93,75 %, statements of some 91.7 %; and for the results of character of students to being honest, responsibility, tolerance and work together in a row the scores were 4 , 4 , 4 and 3.